Sextortion on the Internet: reactions of minors and their vulnerability - Medvedeva, A.S. (Psihologiâ i pravo, 2025)
Context and relevance. The involvement of children and adolescents in sexual Internet communications has become one of the most significant childhood problems for legal psychology. Such interaction leads to adults gaining access to intimate materials of minors, after which they blackmail them. This process (sextortion) has learned to have the maximum destructive impact on the child's psyche, and therefore requires in-depth study. Objective. To analyze the dynamics of sexualized communications between children and adolescents and adult Internet users, to identify and describe the characteristics of minors' response to online blackmail in order to develop measures to prevent their involvement in the process of sextortion. Hypothesis. In a situation of sextortion, children and adolescents show different reactions to blackmail: some take the threats of extortionists seriously, others do not attach any importance to them, some submit and satisfy the demands of the aggressors, while others resist them. Methods and materials. Content analysis of 18 written communications between minors (9 boys and 9 girls aged 9 to 15) and 8 adult online users engaging in sextortion, using descriptive statistics methods. Results. The dynamics of online interaction between adults and minors are described, which includes three stages: first, the child's trust is gained, then the offender encourages him to take nude photographs, after which he carries out sextortion. Three different scenarios of communication of minors in the process of blackmail are identified. Conclusions. In most cases, children and adolescents are motivated to resist sextortion and cut off contact with extortionists, which requires serious effort and a willingness to take risks due to the possibility of «revenge porn». In some cases, minors seek to form friendly relations with extortionists, and, despite blackmail, maintain interaction with them. Measures have been proposed to prevent the involvement of minors in sexualized interactions with Internet users. Контекст и актуальность. Вовлечение детей и подростков в сексуализированные интернет-коммуникации стало одной из наиболее значимых для юридической психологии детства проблем. Подобное взаимодействие нередко приводит к тому, что взрослые люди получают доступ к интимным материалам несовершеннолетних, после чего шантажируют их. Данный процесс (сексторция) способен оказать максимально деструктивное воздействие на психику ребенка, в связи с чем требует углубленного изучения. Цель. Проанализировать динамику сексуализированных коммуникаций детей и подростков со взрослыми интернет-пользователями, выявить и описать особенности реагирования несовершеннолетних на онлайн-шантаж для разработки мер профилактики их вовлечения в процесс сексторции. Гипотеза. В ситуации сексторции дети и подростки проявляют разные реакции на шантаж: кто-то всерьез воспринимает угрозы вымогателей, другие не придают им значения, одни подчиняются и удовлетворяют требования агрессоров, а другие оказывают им сопротивление. Методы и материалы. Контент-анализ 18 письменных коммуникаций несовершеннолетних (9 мальчиков и 9 девочек от 9 до 15 лет) с 8 взрослыми онлайн-пользователями, реализующими сексторцию, с использованием методов описательной статистики. Результаты. Описана динамика онлайн-взаимодействия взрослых людей и несовершеннолетних, которая включает три этапа: сначала происходит завоевание доверия ребенка, затем посягатель побуждает его к съемке в обнаженном виде, после чего реализует сексторцию. Выделены три разных сценария коммуникации несовершеннолетних в процессе шантажа. Выводы. В большинстве случаев дети и подростки мотивированы на сопротивление сексторции и прерывание контакта с вымогателями, что требует от них серьезных усилий и готовности пойти на риск из-за вероятности «порномести». В ряде случаев несовершеннолетние стремятся сформировать дружеские отношения с вымогателями и, несмотря на шантаж, поддерживать взаимодействие с ними. Предложены меры профилактики вовлечения несовершеннолетних в сексуализированное взаимодействие с интернет-пользователями.